CHOOSING CHALLENGES OF AUTHENTIC MATERIALS FOR SPORTSMEN IN LANGUAGE LEARNING - U. O. Azimova (Web of Journals Publishing, 2024)
Present artic devoted to the significance of authentic materials, various types of them, some difficulties of authentic materials in order to choose for sportsmen in language learning.
Keywords: authentic materials, proficiency levels, learning objectives, language exposes learners, language experiences.